2020
DOI: 10.14393/bj-v36n1a2020-42336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sowing time and plant population on the productive potential and agronomic characters in soy

Abstract: Soy is one of the main cultivated species in the world with great economic expression and high impact on Brazilian agribusiness. The productive potential is expressed due to the genetic constitution of the cultivar and the environment in which it is exposed. The market demands for bean production require the ideal handling of the culture in order to optimize the yield potential of the plant. In this context, the handling of the culture is essential to achieve success when cultivating soy. Plant population infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The analysis of biometric indicators at the time of soybean flowering showed that the height of plants changed depending on agricultural practices. The timing of sowing is of decisive importance in the technology of growing crops and largely determines the further growth and development of plants (Luiz et al, 2020;Oserbaeva and Kunakbayev, 2021). The comparison was carried out at three terms of soybean planting, determined by the soil temperature at a depth of 10 cm.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of biometric indicators at the time of soybean flowering showed that the height of plants changed depending on agricultural practices. The timing of sowing is of decisive importance in the technology of growing crops and largely determines the further growth and development of plants (Luiz et al, 2020;Oserbaeva and Kunakbayev, 2021). The comparison was carried out at three terms of soybean planting, determined by the soil temperature at a depth of 10 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Soybeans, like other legumes, require very significant reserves of productive moisture for seed germination and crop formation [6]. The sowing time in growing technology is of decisive importance and largely determines the conditions for the growth and development of soybean plants [7,8]. Excessively loosened soil after plowing, especially in dry conditions, requires additional compaction by rolling [9,10].…”
mentioning
confidence: 99%